2017
DOI: 10.2147/ijn.s136426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the nanoformulation of siRNA-lipid assemblies on their cellular uptake and immune stimulation

Abstract: Two lipid-based nanoformulations have been used to date in clinical studies: lipoplexes and lipid nanoparticles (LNPs). In this study, we prepared small interfering RNA (siRNA)-loaded carriers using lipid components of the same composition to form molecular assemblies of differing structures, and evaluated the impact of structure on cellular uptake and immune stimulation. Lipoplexes are electrostatic complexes formed by mixing preformed cationic lipid liposomes with anionic siRNA in an aqueous environment, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…To our knowledge, this proof-of-concept study is the first systematic comparison of LNPs with saRNA on the interior or exterior of the particles. In order to be able to compare the formulations, we employed a single N/P ratio of 12:1, which can be further optimized for each formulation [37, 38]. It would be particularly useful to characterize the exact distribution of saRNA for each formulation, i.e., whether the saRNA is completely encapsulated or a portion is still accessible on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this proof-of-concept study is the first systematic comparison of LNPs with saRNA on the interior or exterior of the particles. In order to be able to compare the formulations, we employed a single N/P ratio of 12:1, which can be further optimized for each formulation [37, 38]. It would be particularly useful to characterize the exact distribution of saRNA for each formulation, i.e., whether the saRNA is completely encapsulated or a portion is still accessible on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoplexes have not been clinically tested yet, but there is one FDA approved drug utilizing synthetic lipid nanoparticles (LNPs), for hereditary transthyretin amyloidosis. LNPs and lipoplexes share many similar features, but while lipoplexes are slightly bigger in size and formed by binding existing liposomes with nucleic acids, LNPs are rather formed in one step by embedding the nucleic acid with the lipid solution [54]. Currently, LNPs are also being used in two COVID-19 mRNA vaccines used worldwide, and there is an increasing interest in their use as tissue specific therapeutic vehicles for various diseases [55].…”
Section: Novel Inflammation-targeted Molecules For Rna Interference T...mentioning
confidence: 99%
“…Furthermore, encapsulation strategy helps to protect plasmid DNA from the attack of endogenous nucleases [44,110]. Recently, Kobuta et al have reported that encapsulated siRNA within lipid nanoparticles (LNPs) also showed higher stability and cell uptake efficiency as well as low cytotoxicity including reduced release of cytokines (i.e., TNF-α and IL-1β) [111]. However, the encapsulation of plasmid DNA in the aqueous core of liposome is a very tedious process and the encapsulation efficiency is also very low.…”
Section: Intracellular Delivery Of Plasmid Dnamentioning
confidence: 99%